Flows with Return of Water Turbined by a Hydroelectric Power Plant in a Transfer Receiving Basin Using WEAP - Moreno Kimberly Madelen, Ortiz De Orue (2024)
The purpose of this study is to assess the water return flows generated by a hydroelectric power plant that receives water from a transfer system. To achieve this, various tasks were undertaken, including the collection of hydrometeorological data, calculations related to water supply and demand, energy production, and the integration of water flows originating from the transfer. We utilized the WEAP software for this purpose. In an effort to comprehend the current state of the receiving basin for the transfer, an analysis was conducted under different scenarios, including the present state, the driest and wettest years, as well as the scenario of Aricota lagoon with and without water contributions from the Kovire tunnel. This study also underscores the critical importance of managing water resources in transboundary basins for the preservation of essential ecosystems in the region. Furthermore, an evaluation of the water returns flows from the Aricota I and II hydroelectric power plants to the Curibaya River was conducted. As a validation measure for the model, calibration was carried out for the Callazas and Salado rivers, yielding Nash indices of 0.69 and 0.75, respectively. These results affirm the robustness of the model and its capacity to provide reliable data in hydrological simulations.